Location matters: LAG3 levels are lower in renal cell carcinoma metastatic sites compared to primary tumors, and expression at metastatic sites only may have prognostic importance - Schoenfeld, David A.; Merkin, Ross D.; Moutafi, Myrto; Martinez, Sandra; Adeniran, Adebowale; Kumar, Deepika; Jilaveanu, Lucia; Hurwitz, Michael; Rimm, David L.; Kluger, Harriet M. (Frontiers in Oncology, 2022)
While great strides have been made in the treatment of advanced renal cell carcinoma (RCC) with the emergence of immune checkpoint inhibitors (ICIs) and VEGFR-targeting drugs, sizable proportions of patients still do not respond to upfront therapy and long-term responses only occur in a minority of patients. There is therefore a great need for the development of better predictors of response and an increased understanding of mechanism of resistance to these therapies. Alternative immune checkpoints outside the PD-1/PD-L1 axis, such as LAG3, have been implicated as one mechanism of resistance to ICIs. These checkpoints thus represent attractive therapeutic targets, and indeed the LAG3 inhibitor relatlimab was recently approved for the treatment of metastatic melanoma in combination with anti-PD-1 therapy. LAG3 inhibitors are being evaluated for RCC as well. In this context, a better understanding of LAG3 expression patterns in RCC and how they relate to clinicopathologic features of disease and response to immunotherapy may give insight into mechanisms of resistance to PD-1 inhibitors and aid in the identification of subgroups of patients more likely to benefit from certain drug regimens. In this study, we assessed LAG3 protein levels in leukocytes in normal kidney adjacent to RCC, primary RCC tumors, and matched metastatic tumors, including large numbers of brain metastases. We found that LAG3 protein levels are on average lower at metastatic sites compared to matched primary tumors, and that the difference was more pronounced in patients with high-risk clinical characteristics, including those with larger primary tumor size, grade 4 tumors, IMDC poor-risk disease, and initial presentation with brain metastases. We further saw that the prognostic value of LAG3 levels varies depending on the tissue site queried (i.e., primary tumor versus metastases), and that relatively higher LAG3 levels at metastatic sites may predict a better response to immunotherapy and longer overall survival after the development of metastatic disease. These findings may have important implications for the design of future studies involving LAG3 or other immunotherapies in RCC.